Contemporary psychotherapies for a diverse world - Frew, Jon; Spiegler, Michael D (New York : Routledge, 2013)
'This is the first book of its kind to cover the standard counseling theories and integrate multiculturalism into every theory chapter. In addition, every theory chapter is authored by an expert with experience applying individual therapies to a diverse range of clients. Along with traditional theories, the text includes chapters on reality therapy, feminist therapy, and narrative therapy'--
Includes bibliographical references (p. 515-574) and index.
Keywords: Psychotherapy; Cultural psychiatry